Learning experience of undergraduate medical students during ‘model preparation’ of physiological concepts - Soundariya, Krishnamurthy (Korean J Med Educ, 2018)
PURPOSE: Learning physiological concepts and their practical applications in the appropriate contexts remains a great challenge for undergraduate medical students. Hence the present study aimed to analyze the learning experience of undergraduate medical students during an active learning process of ‘preparation of models’ depicting physiological concepts. METHODS: A total of 13 groups, involving 55 undergraduate medical students with three to five individuals in each group, were involved in model preparation. A total of 13 models were exhibited by the students. The students shared their learning experiences as responses to an open-ended questionnaire. The students’ responses were analyzed and generalized comments were generated. RESULTS: Analysis of the results showed that the act of ‘model preparation’ improved concept understanding, retention of knowledge, analytical skills, and referral habits. Further, the process of ‘model preparation’ could satisfy all types of sensory modality learners. CONCLUSION: This novel active method of learning could be highly significant in students’ understanding and learning physiology concepts. This approach could be incorporated in the traditional instructor-centered undergraduate medical curriculum as a way to innovate it.